Mnemonic causation, construction, and the particularity of episodic memory - Sant’Anna, André (Aufklärung: journal of philosophy, 2021)
The idea that episodic memory is memory of particulars is prominent in philosophy. The particularity of remembering, as I will call it, has been taken for granted in most recent theorizing on the subject. This is because the classical causal theory of memory, which has been extremely influential in philosophy, is said to provide a straightforward account of particularity. But the causal theory has been criticized recently, in particular due to its inability to make sense of the constructive character of remembering. In this paper, I argue that recent attempts to account for the constructive character of remembering have failed to account for its particularity. This is either because they depart in important senses from the classical causal theory’s account of mnemonic causation or because they give up on mnemonic causation altogether. I then proceed to consider the question of whether we should go back to the classical causal theory of memory to account for particularity. I argue that, despite the widespread idea that the classical causal theory offers a straightforward account of particularity, there are good reasons to reject it. The upshot is that philosophers of memory should consider alternative accounts of particularity that do not revolve around mnemonic causation.